2010
DOI: 10.1080/10538720903426438
|View full text |Cite
|
Sign up to set email alerts
|

The Open Door Project Task Force: A Qualitative Study on LGBT Aging

Abstract: This paper reports formative qualitative findings from the Open Door Project (ODP), a unique program created by the Lesbian, Gay, Bisexual and Transgender (LGBT) Aging Project. Data were collected from Open Door Task Force members (N = 34). This includes 4 focus groups that were held with a total of 22 participants;and key informant interviews that were conducted with 12 participants from 10 different agencies. Findings revealed that agencies took significant steps to make important and long-lasting structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This was achieved through the development of policies and procedures that are inclusive of LGBT clients, caregivers and staff; development of staff practice skills to implement LGBT inclusive policies; and communicating with community partners, along with current and potential clients, that the organization has a sustained commitment to the inclusion of LGBT clients, caregivers, and staff. Landers, Mimiaga, and Krinsky (2010) conducted a qualitative study of Open Door in its earliest stages (2005)(2006)(2007) and reported that participating agencies made policy changes, implemented staff training, and began developing programs and outreach to LGBT older adults and caregivers. Most respondents indicated that their organization's commitment to, and participation in, Open Door yielded increased recognition and normalization of LGBT issues in their agencies.…”
Section: Creating Change From Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was achieved through the development of policies and procedures that are inclusive of LGBT clients, caregivers and staff; development of staff practice skills to implement LGBT inclusive policies; and communicating with community partners, along with current and potential clients, that the organization has a sustained commitment to the inclusion of LGBT clients, caregivers, and staff. Landers, Mimiaga, and Krinsky (2010) conducted a qualitative study of Open Door in its earliest stages (2005)(2006)(2007) and reported that participating agencies made policy changes, implemented staff training, and began developing programs and outreach to LGBT older adults and caregivers. Most respondents indicated that their organization's commitment to, and participation in, Open Door yielded increased recognition and normalization of LGBT issues in their agencies.…”
Section: Creating Change From Resultsmentioning
confidence: 99%
“…In addition, Massachusetts's 2004 legalization of same-sex marriage, and subsequent legal appeals, brought LGBT issues to the general public's consciousness and the implications of marriage equality were considered in many arenas, including elder services. Some agencies incorporated Open Door's message of LGBT inclusion into their ongoing Downloaded by [University of Nebraska, Lincoln] at 06:21 05 April 2015 diversity efforts and others used it as a starting point for addressing inclusion of other less dominant populations they serve (Landers et al, 2010).…”
Section: Creating Change From Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This important early stage of intervention by health workers is a missed opportunity to support older LGBTI people when receiving aged and end-of-life care. Recommendations from the research have been made regarding educating health care workers towards the specific needs of older LGBTI people and to create non-heteronormative assessment processes for all older people interfacing with health care and end-of-life care (Hughes, 2009;Hughes & Kentlyn, 2011;Landers, Mimiaga & Krinsky, 2010;Stein et al, 2010). Hughes (2009) suggests that LGBTI specific posters and leaflets that are visible in health care settings would go some way towards creating a safe and inclusive environment for older LGBTI people and health care workers could be using more supportive and inclusive language during initial assessments.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…29 Ongoing competency training for staff is essential. 40 One study found that providing LGBT aging sensitivity training to service providers resulted in positive change at least in the short term. 41 A first step in developing sensitivity and understanding is exploring one's own homophobic or heterosexist biases.…”
mentioning
confidence: 99%